Implementation automatic dependent surveillance broadcasting (ADS-B) modulation and demodulation on USRP ETTUS [electronic resource] - Cheong, Xin Lin, 1991- , author; Ahmad Zuri Sha'ameri , supervisor; Fakulti Kejuruteraan Elektrik (2015)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2015